2020
DOI: 10.1007/s41348-020-00378-y
|View full text |Cite
|
Sign up to set email alerts
|

Wheat blast caused by Magnaporthe oryzae pathovar Triticum is efficiently controlled by the plant defence inducer isotianil

Abstract: Wheat blast caused by Magnaporthe oryzae pv. Triticum is an upcoming threat to wheat cultivation worldwide. The disease crossing over to wheat first gained attention in South America, with increasing interest coming from its more recent appearance in the big wheat-growing areas of Asia. The increasing economic relevance of the disease and the lack of genetic resistance in current wheat breeding material, besides fungicide resistance already present in fungal pathogen populations, highlighted the need to evalua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In this sense, Lahlali et al [39,40] found that mechanistically, the determination of the expression of selected defense genes pointed to the activation of JA-and ET-related defense pathways in B. napus. A similar mechanism to induce defense is associated with the compound isotianil [17][18][19]. Therefore, we could show that both control agents are potential new tools to reduce clubroot disease in oilseed rape.…”
Section: Infection-related Changes In Response To Host Plantsmentioning
confidence: 88%
See 1 more Smart Citation
“…In this sense, Lahlali et al [39,40] found that mechanistically, the determination of the expression of selected defense genes pointed to the activation of JA-and ET-related defense pathways in B. napus. A similar mechanism to induce defense is associated with the compound isotianil [17][18][19]. Therefore, we could show that both control agents are potential new tools to reduce clubroot disease in oilseed rape.…”
Section: Infection-related Changes In Response To Host Plantsmentioning
confidence: 88%
“…However, its particular mode of action was better understood only during the last decade. Bektas and Eulgem [18] as well as Portz et al [19] showed that isotianil can act like an elicitor that mimics salicylic acid with significant activity against blast diseases in rice and wheat but without having a direct effect against these diseases. Similarly, isotianil can help to reduce difficult-to-control diseases like Fusarium wilt of banana caused by the fungal agent Fusarium oxysporum f. sp.…”
Section: Introductionmentioning
confidence: 99%
“…Their applications, chemistry and synthesis have been reviewed [17][18][19]. Examples of biologically useful isothiazoles are the fungicide isotianil (Stout ® ) [20,21], active against rice blast, and the antibacterial drug sulfasomizole [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The control of blast disease is difficult and mainly achieved through the use of chemical fungicides [ 5 , 25 ]. However, extensive use of chemical fungicides has resulted in development of resistance in fungus against the fungicides [ 5 , 11 , 45 ]. Resistance sources for breeding blast resistance are limited in some cases such as in wheat.…”
Section: Introductionmentioning
confidence: 99%